2006
DOI: 10.1186/1475-2875-5-43
|View full text |Cite
|
Sign up to set email alerts
|

Artemether-lumefantrine versus artesunate plus amodiaquine for treating uncomplicated childhood malaria in Nigeria: randomized controlled trial

Abstract: Background: The therapeutic efficacy of artesunate plus amodiaquine and artemether/ lumefantrine were assessed in an area of Nigeria with high levels of Plasmodium falciparum resistance to chloroquine and sulphadoxine-pyrimethamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…After risk of bias assessment, 7 studies were of high risk [23-25,34-37]. The age of the patients ranged between six weeks and 18 years (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After risk of bias assessment, 7 studies were of high risk [23-25,34-37]. The age of the patients ranged between six weeks and 18 years (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies involving 6018 children comparing AL with ASAQ were included and analysed [20,26-37]. The risk of SAEs was not significantly different for both treatment groups (p = 0.07 RR: 0.54, 95% CI: 0.27-1.05).…”
Section: Resultsmentioning
confidence: 99%
“…Soluplus shows exceptional solubilizing properties for BCS class II and class IV drugs and also offers the possibility of producing solid dispersions by hot-melt extrusion [13]. The dissolution of poorly soluble drugs in aqueous media can be highly improved by the use of solid dispersions with Soluplus [14].…”
Section: Introductionmentioning
confidence: 99%
“…This study did not compare artemisinin- naphthoquine with another ACT, but an earlier study in the same locality showed comparable cure rates for artemether-lumefantrine (87.0%) and artesunate/amodiaquine (82.5%) [18]. The rapid decrease in the number of persons with parasitaemia by Day 2 of follow-up is indicative of the high therapeutic efficacy characteristic of other forms of ACT already in use.…”
Section: Discussionmentioning
confidence: 93%